Age‐specific incidence rates for breast cancer in carriers of BRCA1 mutations from Norway. (1st March 2012) - Møller, P; Mæhle, L; Vabø, A; Clark, N; Sun, P; Narod, SA
<x xml:space="preserve">Abstract</x> Møller P, Mæhle L, Vabø A, Clark N, Sun P, Narod SA. Age‐specific incidence rates for breast cancer in carriers of BRCA1 mutations from Norway. Incidence rates of breast cancer among women with a BRCA1 mutation vary according to their reproductive histories and country of residence. To measure cancer incidence, it is best to follow‐up cohort of healthy women prospectively. We followed up a cohort of 675 women with a BRCA1 mutation who did not have breast or ovarian cancer before inclusion and who had a normal clinical examination and mammography at first visit. After a mean of 7.1 years, 98 incident cases of breast cancer were recorded in the cohort. Annual cancer incidence rates were calculated, and based on these, a penetrance curve was constructed. The average annual cancer risk for the Norwegian women from age 25 to 70 was 2.0%. Founder mutations had lower incidence rate (1.7%) than less frequent mutations (2.5%) (p = 0.03). The peak incidence (3.1% annual risk) was observed in women from age 50 to 59. The age‐specific annual incidence rates and penetrance estimate were compared with published figures for women from North America and from Poland. The risk of breast cancer to age 70 was estimated to be 61% for women from Norway, compared with 55% for women from Poland and 69% for women from North America.